KOMPLEKSITAS PENERAPAN APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DALAM RANGKA PENCATATAN IDENTITAS KEPENDUDUKAN DI KABUPATEN NGANJUK - Nafiah, Nurin; Oktariyanda, Trenda Aktiva (Publika, 2024)
The implementation of E-government can influence the sustainability of services for the future. The Director General of the Population and Civil Registration Service of the Ministry of Home Affairs created the IKD application as a form of transforming physical KTPs into digital KTPs to make it easier for people to provide digital public services and prevent data leaks. In implementing the IKD application, complexities are still found, such as a lack of public understanding regarding IKD, network systems that often have errors in the IKD application, and limited smartphones in one Family Card (KK). This research aims to describe the implementation of the IKD application in Nganjuk Regency. This research focuses on the theory of E-government innovation by Choi and Chandler (2020), namely the background to the occurrence of E-government innovation, the introduction of E-government which consists of 2 indicators, namely preliminary structure and preliminary behavior, E-government implementation factors. This research uses a descriptive method with a qualitative approach. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that in the implementation of the IKD application there are still problems such as there are still many people in Nganjuk district who are still not familiar with technology, apart from that there are still people who do not know about IKD innovation because the socialization carried out by the Nganjuk Regency Population and Civil Registry Office is not evenly distributed, and the IKD innovation system is still frequent. errors that can hinder the development of IKD innovation. This IKD innovation is not effective if it is operated on elderly people and people with disabilities who cannot make good use of this IKD application. This research suggests improvements to the IKD application system which often has errors and increasing outreach to the community.